Análisis de costos en la labor de fertilización en el sostenimiento del cultivo de caña de azúcar en el ingenio monterrey - BRAVO SANCHEZ, NELSON FABIAN (2014)
This research work is entitled “Analysis of Costs in the Work of Fertilization in the Sustaining of the Cultivation of Sugar Cane in the Ingenio Monterrey”, with the purpose of giving a contribution to the Superintendence of Field arose the following objectives: Analyze the costs in the work of fertilization in the sustainability of the cultivation of sugar cane in the Ingenio Monterrey, Determine the real costs of fertilization per hectare in the cultivation of sugar cane, Compare costs and the production obtained in recent years per hectare in the crop and Determine the profitability with reduced costs of inputs into the work of fertilization. Once obtained the production costs during the period 2011-2013; an analysis and comparative historical in order to determine the increase in the costs of fertilization, supplies, machinery and labor recommended by an external consulting having as ultimate goal to increase production per ton of cane. Within the intervention of improvement plan it was decided to intervene with a reduction of costs on inputs from fertilization, changing the formulation given by the consultancy with the traditional formula based on Nitrogen, Phosphorous and Potassium; there is no significant changes in production during the period of this research study. Among the results, product of the financial analysis carried out in the fertilization was determinate that costs in this work in the Ingenio Monterrey during the period 2011-2013 increased 160%, which has represented the 8% increase in production volume. To make profitable the change of formulation in fertilization, this 8% increase in volume must compensate for 160% of the cost of this new formulation in fertilizers considering the national retail price of sugar pack. As the final result was determined that additional expenditure by increasing in puts in the fertilization is not justified, since earnings per ton of cane in 2012 was $8.36 USD less than the 2011 $8.92 USD. By obtaining results is given compliance to financial analysis in the work of fertilization in the sustainability of the cultivation of sugar cane in the Ingenio Monterrey wit so that through this research it can take corrective actions for the benefit of the sugar company.